PEMANFAATAN FLY ASH DAN LIMBAH BAJA SEBAGAI BAHAN ALTERNATIF PANEL DINDING - Lilis Tiyani; Sukarman; Nunung Martina (Jurnal Ilmiah Teknologi Infomasi Terapan, 2026)
This study aims to evaluate the effect of steel waste addition on the mechanical properties of fly ash-based wall panels as part of developing environmentally friendly construction materials. The main materials used include sand, fly ash, sodium silicate (Na₂SiO₃) solution, sodium hydroxide (NaOH) solution, and steel waste. The manufacturing process involved preparing the activator, mixing dry materials (sand, fly ash, and steel waste), gradually adding the activator, molding, and curing under moist conditions. The test results showed that panels containing steel waste achieved a compressive strength of 15.91 MPa, an increase of 22% compared to panels without steel waste (13.04 MPa). The flexural strength of panels with steel waste reached 4.93 MPa, an increase of 64% compared to those without (3.01 MPa). The strength enhancement is attributed to the role of steel waste particles as micro-reinforcement, which improves the microstructure, increases density, and prevents crack propagation. Therefore, incorporating steel waste into fly ash-based wall panels effectively enhances mechanical performance while supporting the development of sustainable building materials.